Anti-blue-light nano-material, spectacle lens containing same and preparation method of anti-blue-light nano-material
By using titanium titanium dioxide nano -doped nano -doped nano -mixed in the glasses, the existing anti -blue light glasses have poor effects and high production costs when filtering high -energy blue light, and realized the reduction of precision filtering and production costs of high -energy blue light. Essence
Patent Information
- Application Number
- CN202411483109.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Existing anti-blue light glasses are not effective when filtering high-energy blue light and have high production costs, which affects their popularity and use.
Iron ion-doped titanium dioxide is used as an anti-blue light nanomaterial and is evenly dispersed in the polymer optical base material of spectacle lenses to accurately filter high-energy blue light in the 400nm to 430nm band while maintaining transparency to other wavelength bands. pass rate.
Achieve precise filtering of high -energy blue light, reduce the damage to the eyes, reduce production costs, and improve the transparency and mechanical performance of the optical lenses.
Smart Images

Figure CN119350708A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of protective materials, and in particular to a blue light protection nano material, an eyeglass lens containing the same, and a preparation method thereof. Background Art
[0002] With the increasing popularity of electronic products such as computers and mobile phones, modern people's work and study are inseparable from these electronic products. Staring at electronic products for a long time can cause patients to experience eye fatigue, dryness, difficulty opening eyes, photophobia and other phenomena.
[0003] In response to the above problems, anti-blue light glasses have appeared on the market. These glasses usually have special lens coatings or filter layers to filter out some blue light, thereby reducing eye fatigue and discomfort that may be caused by facing the screen for a long time. However, the quality of existing anti-blue light glasses varies. Some anti-blue light glasses reduce light transmittance due to filtering too much blue light, which affects the visual experience and even increases visual fatigue. In addition, the damage that blue light emitted by electronic products may cause to the eyes is mainly concentrated in the short-wave blue light range. This band range is usually: 400nm to 430nm. The blue light in this band is high-energy blue light and is considered to have greater potential harm to the eyes. The anti-blue light glasses on the market have poor precision filtering effect on blue light in this band. In other words, it is difficult for anti-blue light glasses to achieve precise filtering of high-energy blue light at present. In the process of anti-blue light, it will also filter visible light in its band. It is difficult to balance anti-blue light and unaffected other light entering the eye in actual scenes. In addition, in order to enhance the anti-blue light effect, the current anti-blue light glasses use an anti-blue light film layer to filter blue light. This type of lens requires a more complex production process, has high production costs, and has a high market price, which is not conducive to promotion and use. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a blue light blocking nanomaterial and an eyeglass lens containing the same and a preparation method thereof, which solves the technical problems of poor accurate blue light blocking effect and high production cost of existing blue light blocking glasses.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0008] In a first aspect, an embodiment of the present invention provides a blue light protection nanomaterial, which is titanium dioxide doped with iron ions, wherein the total content of iron atoms is 1%-4%; and the particle size of the nanomaterial is 20-50nm.
[0009] In a second aspect, an embodiment of the present invention provides an eyeglass lens comprising the anti-blue light nanomaterial and a polymer optical substrate as described in the first aspect; the anti-blue light nanomaterial is uniformly dispersed in the polymer optical substrate, wherein the mass ratio of the anti-blue light nanomaterial to the polymer optical substrate is 1-3‰.
[0010] As a preferred embodiment of the present invention, the spectacle lens, the polymer optical substrate is one or more of methacrylate resin, polyurethane resin, allyl diglycol dicarbonate resin, acrylate resin and epoxy acrylate resin.
[0011] As a preferred embodiment of the present invention, the eyeglass lens further comprises an ultraviolet absorber in an amount of 1-4‰ of the mass ratio of the polymer optical substrate.
[0012] As a preferred embodiment of the present invention, in the eyeglass lens, the ultraviolet absorber is a fat-soluble ultraviolet absorber selected from one or more of UV-326, UV-327, UV-329, UV-360, and UV-531.
[0013] As a preferred embodiment of the present invention, the eyeglass lens further includes an initiator whose mass ratio to the polymer optical substrate is 1-3‰; the initiator is selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl peroxide, diisopropyl peroxide, di-tert-butyl peroxide, diisopropyl peroxydicarbonate, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, methyl benzoylformate, benzoin dimethyl ether, diphenylacetophenone, α-aminoalkylphenone, dibenzoylphenylphosphine oxide, benzophenone and isopropylthioxanthone; and a dispersion medium whose mass ratio to the polymer optical substrate is 10-15‰; the dispersion medium is styrene.
[0014] Among them, colorless and transparent styrene liquid is used as the dispersion medium to fully disperse the anti-blue light nanomaterial, prevent the agglomeration of the anti-blue light nanomaterial particles, ensure the subsequent dispersion effect of the anti-blue light nanomaterial, and then ensure the uniformity of the anti-blue light function of the lens. At the same time, the dispersion medium has good transparency and does not affect the color and optical properties of the final lens.
[0015] In the third aspect, an embodiment of the present invention provides a method for preparing an eyeglass lens, comprising the following steps: S1. Dispersion of anti-blue light nanomaterials: mixing the anti-blue light nanomaterials with a liquid dispersion medium to obtain an anti-blue light nanomaterial dispersion; S2. First curing reaction: stirring and mixing the dispersion with a polymer optical monomer and an initiator evenly, then vacuum degassing, placing the lens into a mold, reacting and curing according to a first temperature rise program, and demolding to obtain a primary lens; S3. Second curing reaction: placing the primary lens into a mold again, reacting and curing according to a second temperature rise program to obtain an eyeglass lens containing anti-blue light nanomaterials.
[0016] As a preferred embodiment of the present invention, in the method for preparing the eyeglass lens, in S1, the mass ratio of the anti-blue light nanomaterial to the dispersion medium is 1-3:10; the process of mixing the anti-blue light nanomaterial and the dispersion medium is: heating to 70-90°C while stirring, and then ultrasonically dispersing for 40-50 minutes.
[0017] Among them, the mass ratio of the anti-blue light nanomaterial to the dispersion medium is 1-3:10. The process of mixing the anti-blue light nanomaterial and the dispersion medium is to heat up to 70-90°C while stirring, and then ultrasonically disperse for 40-50 minutes to further ensure the uniform dispersion of the nanomaterial. At the same time, the dispersion medium styrene reacts with the polymer optical monomer. During the polymerization of the polymer optical monomer, the uniform distribution of the anti-blue light nanomaterial in the polymer can be promoted. At the same time, styrene itself undergoes a polymerization reaction to generate transparent polystyrene, which is entangled with the polymer optical material that constitutes the lens. Polystyrene has excellent optical properties, and the benzene ring it contains limits the rotational freedom of the polymer molecular chain, thereby increasing the overall rigidity of the lens material and improving the mechanical properties and thermal stability of the lens.
[0018] As a preferred embodiment of the present invention, in the method for preparing the eyeglass lens, in S2, the polymer optical monomer is selected from one or more of methacrylate monomers, polyurethane monomers, allyl diglycol dicarbonate monomers, acrylate monomers, and epoxy acrylate monomers.
[0019] As a preferred embodiment of the present invention, in the method for preparing the eyeglass lens, in S2, the first temperature rising procedure is the gelling stage; and in S3, the second temperature rising procedure is the post-curing stage.
[0020] In the gelation stage, a continuous stage-by-stage heating and cooling process within a relatively low temperature range is adopted. The optical monomers begin to polymerize to form a three-dimensional network structure. The reactants gradually lose fluidity and transform into a semi-solid state, i.e., a gel state, which provides a basic cross-linking density for the subsequent post-curing stage. In the post-curing stage, a continuous stage-by-stage heating and cooling process within a temperature range higher than that in the gelation stage is adopted to further increase the cross-linking density of the material. The two stages cooperate with each other to enable the final prepared eyeglass lenses to obtain higher mechanical strength and thermal stability.
[0021] At the same time, both stages of the curing reaction undergo continuous stage-by-stage temperature increases. By gradually increasing the temperature, the rate of the polymerization reaction can be gradually accelerated, which helps to control the molecular weight distribution and structure of the polymer, ensure the uniform distribution of the anti-blue light nanomaterials, and optimize the lens performance.
[0022] (III) Beneficial effects
[0023] The beneficial effects of the present invention are as follows: the anti-blue light nanomaterial and the eyeglass lens containing the same and the preparation method thereof of the present invention use titanium dioxide doped with iron ions as the anti-blue light nanomaterial and evenly disperse it in the lens, wherein the total content of iron atoms in the nanomaterial is 1%-4%. Compared with the prior art, it can accurately filter high-energy blue light in the band of 400nm to 430nm, while not affecting the transmittance of the eyeglass lens to light in other bands, thereby restoring the real light scene to the greatest extent. After wearing the eyes, it has a significant alleviating effect on the symptoms of dry eyes and astringent eyes caused by long-term use of mobile phones and computers, thereby achieving precise protection of the eyes. In addition, the lens production process is simple, the cost is low, and it has a good prospect for promotion and application.
[0024] The eyeglass lens also includes an ultraviolet absorber in a mass ratio of 1-4‰ of the polymer optical substrate. The ultraviolet absorber is used to absorb the ultraviolet part in sunlight and fluorescent light sources to protect the eyes from ultraviolet damage. At the same time, it effectively prevents the aging effect of the lens material in a long-term ultraviolet environment and increases the service life of the lens.
[0025] In the preparation method of the eyeglass lens, before the anti-blue light nanomaterial participates in the polymerization reaction step of the polymer optical monomer, the anti-blue light nanomaterial is fully dispersed using a liquid dispersion medium to prevent the agglomeration of the anti-blue light nanomaterial particles and ensure the subsequent dispersion effect of the anti-blue light nanomaterial; the mass ratio of the anti-blue light nanomaterial to the dispersion medium is 1-3:10, and the process of mixing the anti-blue light nanomaterial and the dispersion medium is to heat up to 70-90°C while stirring, and then ultrasonically disperse for 40-50 minutes, so as to further ensure the uniform dispersion of the nanomaterial, thereby ensuring the uniformity of the anti-blue light function of the eyeglass lens.
[0026] At the same time, the dispersion medium styrene reacts with the polymer optical monomer. During the polymerization of the polymer optical monomer, it can promote the uniform distribution of the anti-blue light nanomaterial in the polymer. At the same time, the reaction of styrene and the polymer optical monomer can ultimately improve the mechanical properties of the lens.
[0027] The dispersion of the blue light protection nanomaterial is stirred and mixed evenly with the polymer optical monomer and the initiator, and then vacuum degassed to improve the product quality of the eyeglass lens.
[0028] Both stages of the curing reaction are heated in continuous stages. By gradually increasing the temperature, the rate of the polymerization reaction can be gradually accelerated, which helps to control the molecular weight distribution and structure of the polymer, ensure the uniform distribution of the anti-blue light nanomaterial, and optimize the lens performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an EDS analysis result diagram of the blue light protection nanomaterial prepared in Example 1 of the present invention;
[0030] Figure 2 This is an EDS analysis result diagram of the blue light protection nanomaterial prepared in Example 2 of the present invention;
[0031] Figure 3 This is an EDS analysis result diagram of the blue light protection nanomaterial prepared in Example 3 of the present invention;
[0032] Figure 4 This is a spectrum analysis diagram of the eyeglass lens prepared in Example 4 of the present invention after filtering;
[0033] Figure 5 This is a spectrum analysis diagram of the eyeglass lens prepared in Example 5 of the present invention after filtering;
[0034] Figure 6 This is a spectrum analysis diagram of the eyeglass lens prepared in Example 6 of the present invention after filtering;
[0035] Figure 7 This is a spectrum analysis diagram of the eyeglass lens prepared in Example 7 of the present invention after filtering;
[0036] Figure 8 This is a spectrum analysis diagram of the eyeglass lens prepared in Example 8 of the present invention after filtering;
[0037] Fig. 9 This is a spectrum analysis diagram of the eyeglass lens prepared in Example 9 of the present invention after filtering;
[0038] Fig.10 This is a spectrum analysis diagram of the eyeglass lens prepared in Comparative Example 1 of the present invention after filtering. DETAILED DESCRIPTION
[0039] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0040] The embodiments of the present invention propose a blue light-proof nanomaterial, a spectacle lens containing the same, and a preparation method thereof, which are aimed at the poor protection effect of existing blue light-proof glasses and the high production cost. Titanium dioxide doped with iron ions is used as the blue light-proof nanomaterial, and it is evenly dispersed in the lens, wherein the total content of iron atoms in the nanomaterial is 1%-4%. Compared with the prior art, it can accurately filter high-energy blue light in the band of 400nm to 430nm, while not affecting the transmittance of the spectacle lens to light in other bands, and restore the real light scene to the greatest extent. After wearing the eyes, it has a significant alleviating effect on the symptoms of dry eyes and astringent eyes caused by long-term use of mobile phones and computers, thereby achieving precise protection of the eyes. In addition, the lens production process is simple, the cost is low, and it has a good prospect for promotion and application.
[0041] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0042] Example 1
[0043] This embodiment provides a method for preparing a blue light blocking nanomaterial, and the specific steps are as follows:
[0044] (1) Take 250 g of ultrapure water, add 30 g of titanium sulfate, 10 g of ferric nitrate, and 50 g of ethanol, stir evenly, and perform ultrasound to obtain material A.
[0045] (2) Take 250 g of ultrapure water, add 10 g of ammonia water and 20 g of 2-aminoterephthalic acid, stir evenly and perform ultrasound to obtain material B.
[0046] (3) Slowly add material B to material A under stirring conditions. When a milky white or yellow precipitate appears in material A, continue stirring for 30 minutes to allow materials AB to fully react.
[0047] (4) After the reaction of material A and material B is completed, the precipitate is filtered with a 1 micron filter membrane to obtain a blue light-proof nanomaterial, which is placed in an oven and dehydrated and dried at 100° C. for 12 hours to obtain a block of iron ion-doped titanium dioxide.
[0048] (5) The blocky iron ion-doped titanium dioxide is crushed by a crusher to obtain a powdery iron ion-doped titanium dioxide nanomaterial.
[0049] The obtained iron-titanium bimetallic oxide nanomaterials were analyzed for their constituent elements using the Energy Dispersive X-ray Spectroscopy (EDS) method. The analysis results are as follows: Figure 1 The specific atomic content of the corresponding elements is shown in Table 1.
[0050] Example 2
[0051] This embodiment provides a method for preparing a blue light blocking nanomaterial, and the specific steps are as follows:
[0052] (1) Take 300 g of ultrapure water, add 35 g of titanium sulfate, 15 g of ferric nitrate, and 60 g of ethanol, stir evenly, and perform ultrasound to obtain material A.
[0053] (2) Take 300 g of ultrapure water, add 13 g of ammonia water and 25 g of 2-aminoterephthalic acid, stir evenly and perform ultrasound to obtain material B.
[0054] (3) Slowly add material B to material A under stirring conditions. When a milky white or yellow precipitate appears in material A, continue stirring for 40 minutes to allow materials AB to fully react.
[0055] (4) After the reaction of material A and material B is completed, the precipitate is filtered with a 1 micron filter membrane to obtain a blue light-proof nanomaterial, which is placed in an oven and dehydrated and dried at 110° C. for 10 hours to obtain a block of iron ion-doped titanium dioxide.
[0056] (5) The blocky iron ion-doped titanium dioxide is crushed by a crusher to obtain a powdery iron ion-doped titanium dioxide nanomaterial.
[0057] The obtained iron-titanium bimetallic oxide nanomaterials were analyzed for their constituent elements using the Energy Dispersive X-ray Spectroscopy (EDS) method. The analysis results are as follows: Figure 2 The specific atomic content of the corresponding elements is shown in Table 1.
[0058] Example 3
[0059] This embodiment provides a method for preparing a blue light blocking nanomaterial, and the specific steps are as follows:
[0060] (1) Take 350 g of ultrapure water, add 40 g of titanium sulfate, 20 g of ferric nitrate, and 70 g of ethanol, stir evenly, and perform ultrasound to obtain material A.
[0061] (2) Take 350 g of ultrapure water, add 16 g of ammonia water and 30 g of 2-aminoterephthalic acid, stir evenly and perform ultrasound to obtain material B.
[0062] (3) Slowly add material B to material A under stirring conditions. When a milky white or yellow precipitate appears in material A, continue stirring for 50 minutes to allow materials AB to fully react.
[0063] (4) After the reaction of material A and material B is completed, the precipitate is filtered with a 1 micron filter membrane to obtain a blue light-proof nanomaterial, which is placed in an oven and dehydrated and dried at 120° C. for 8 hours to obtain a block of iron ion-doped titanium dioxide.
[0064] (5) The blocky iron ion-doped titanium dioxide is crushed by a crusher to obtain a powdery iron ion-doped titanium dioxide nanomaterial.
[0065] The obtained iron-titanium bimetallic oxide nanomaterials were analyzed for their constituent elements using the Energy Dispersive X-ray Spectroscopy (EDS) method. The analysis results are as follows: Figure 3 The specific atomic content of the corresponding elements is shown in Table 1.
[0066] Table 1
[0067]
[0068] Example 4
[0069] This embodiment provides a method for preparing an eyeglass lens, and the specific steps are as follows:
[0070] (1) 50 g of styrene and 5 g of iron ion-doped titanium dioxide nanomaterial (prepared in Example 3) were added to a beaker, heated to 70° C. while stirring, and dispersed in an ultrasonic disperser for 30 minutes to obtain a light yellow transparent nanomaterial dispersion.
[0071] (2) Add 5 kg of acrylic acid ester monomer, 5 g of initiator azobisisobutyronitrile, 5 g of ultraviolet absorber UV329 and the nanomaterial dispersion of step (1) into a stirring and pouring bucket, stir and mix at room temperature for 30 min to obtain a mixture, and then vacuum the mixture at 20° C. for 30 min to remove bubbles in the mixture.
[0072] Gelation stage;
[0073] In S3, the second temperature rise program is the post-curing stage
[0074] (3) The mixture after degassing is then poured into a glass mold cavity, moved into a programmed temperature furnace, and heated for gelation reaction according to the following program: from room temperature to 35°C after 10 minutes, then to 38°C after 6 hours, then to 48°C after 6 hours, then to 73°C after 3 hours, then to 98°C after 4 hours and maintained for 2 hours, and finally cooled to 70°C after 1 hour; after the initial curing is completed, the mold is demolded to obtain a primary lens.
[0075] (4) The primary lens is cleaned and trimmed, and then placed in a programmed temperature furnace again, and subjected to a post-curing reaction (secondary curing) by heating according to the following program: heating from 30°C to 105°C over 3 hours and maintaining for 2 hours, and then cooling to 30°C over 2 hours; thereby obtaining an eyeglass lens with the function of relieving dry eyes.
[0076] The light transmittance of the eyeglass lenses was analyzed by UV-visible spectrophotometer. Figure 4 The lens surface mechanical properties were tested, and the test results are shown in Table 1.
[0077] Example 5
[0078] This embodiment provides a method for preparing an eyeglass lens, which is different from Embodiment 4 in that:
[0079] In step (1), 100 g of styrene and 20 g of iron ion-doped titanium dioxide nanomaterial (prepared in Example 3) were added to a beaker, heated to 80° C. while stirring, and then dispersed in an ultrasonic disperser for 40 minutes to obtain a light yellow transparent nanomaterial dispersion.
[0080] In step (2), 10 kg of acrylic acid ester monomer, 20 g of azobisisobutyronitrile, 20 g of ultraviolet absorber UV329 and the nanomaterial dispersion of step (1) are added to a stirring and pouring bucket, and stirred and mixed at room temperature for 40 minutes to obtain a mixture. The remaining steps remain unchanged.
[0081] The light transmission performance of the light beam passing through the finished eyeglass lens is analyzed by UV-visible spectrophotometer. Figure 5 The lens surface mechanical properties were tested, and the test results are shown in Table 1.
[0082] Example 6
[0083] This embodiment provides a method for preparing an eyeglass lens, which is different from Embodiment 4 in that:
[0084] In step (1), 150 g of styrene and 45 g of iron ion-doped titanium dioxide nanomaterial (prepared in Example 3) were added to a beaker, heated to 90° C. while stirring, and then dispersed in an ultrasonic disperser for 50 minutes to obtain a light yellow transparent nanomaterial dispersion.
[0085] In step (2), 15 kg of acrylic acid ester monomer, 45 g of azobisisobutyronitrile, 45 g of ultraviolet absorber UV329 and the nanomaterial dispersion of step (1) are added to a stirring and pouring bucket, and stirred and mixed at room temperature for 40 minutes to obtain a mixture. The remaining steps remain unchanged.
[0086] The light transmission performance of the light beam passing through the finished eyeglass lens is analyzed by UV-visible spectrophotometer. Figure 6 The lens surface mechanical properties were tested, and the test results are shown in Table 1.
[0087] Example 7
[0088] This embodiment provides a method for preparing an eyeglass lens, which is different from Embodiment 4 in that:
[0089] In step (2), 5 kg of epoxy acrylate monomer, 5 g of azobisisobutyronitrile, 5 g of ultraviolet absorber UV329 and the nanomaterial dispersion of step (1) are added to a stirring and pouring bucket, and the mixture is stirred at room temperature for 30 minutes to obtain a mixture.
[0090] In step (3), the mixture after degassing is poured into a glass mold cavity, moved into a program heating furnace, and cured according to the following program heating reaction: 37°C for 30 minutes, 45°C for 1.5 hours, 55°C for 7 hours, 65°C for 6 hours, 75°C for 2 hours, 105°C for 3 hours, and 78°C for constant temperature; demolding after curing to obtain a primary lens. The remaining steps remain unchanged.
[0091] The light transmission performance of the light beam passing through the finished eyeglass lens is analyzed by UV-visible spectrophotometer. Figure 7 The lens surface mechanical properties were tested, and the test results are shown in Table 1.
[0092] Example 8
[0093] This embodiment provides a method for preparing an eyeglass lens, which is different from Embodiment 7 in that:
[0094] In step (1), 100 g of styrene and 20 g of iron ion-doped titanium dioxide nanomaterial (prepared in Example 3) were added to a beaker, heated to 80° C. while stirring, and then dispersed in an ultrasonic disperser for 40 minutes to obtain a light yellow transparent nanomaterial dispersion.
[0095] In step (2), 10 kg of epoxy acrylate monomer, 20 g of azobisisobutyronitrile, 20 g of UV absorber UV329 and the nanomaterial dispersion of step (1) are added to a stirring and pouring bucket, and stirred and mixed at room temperature for 40 minutes to obtain a mixture. The remaining steps remain unchanged.
[0096] The light transmission performance of the light beam passing through the finished eyeglass lens is analyzed by UV-visible spectrophotometer. Figure 8 The surface mechanical properties of the finished spectacle lenses were tested, and the test results are shown in Table 1.
[0097] Example 9
[0098] This embodiment provides a method for preparing an eyeglass lens, which is different from Embodiment 7 in that:
[0099] In step (1), 150 g of styrene and 45 g of iron ion-doped titanium dioxide nanomaterial (prepared in Example 3) were added to a beaker, heated to 90° C. while stirring, and then dispersed in an ultrasonic disperser for 50 minutes to obtain a light yellow transparent nanomaterial dispersion.
[0100] In step (2), 15 kg of epoxy acrylate monomer, 45 g of azobisisobutyronitrile, 45 g of UV absorber UV329 and the nanomaterial dispersion of step (1) are added to a stirring and pouring bucket, and stirred and mixed at room temperature for 40 minutes to obtain a mixture. The remaining steps remain unchanged.
[0101] The light transmission performance of the light beam passing through the finished eyeglass lens is analyzed by UV-visible spectrophotometer. Fig. 9 The surface mechanical properties of the finished spectacle lenses were tested, and the test results are shown in Table 1.
[0102] Comparative Example 1
[0103] This comparative example provides a method for preparing a spectacle lens, which differs from Example 4 in that:
[0104] In step (1), 5 g of the iron ion-doped titanium dioxide nanomaterial is replaced with a mixture of iron oxide nanopowder and titanium dioxide nanopowder, wherein the atomic ratio of iron to titanium in the iron oxide and titanium dioxide is consistent with the atomic ratio of iron to titanium in the iron ion-doped titanium dioxide nanomaterial in Example 4. The remaining steps remain unchanged.
[0105] The light transmission performance of the light beam passing through the finished eyeglass lens is analyzed by UV-visible spectrophotometer. Fig.10 .
[0106] Comparative Example 2
[0107] This comparative example provides a method for preparing an eyeglass lens, which differs from Example 4 in that in step (1), the dispersion medium styrene is replaced by methyl methyl propionate.
[0108] The finished spectacle lenses finally had granular regions inside and could not be used normally. The reason was that methyl methacrylate, as a dispersion medium, could not disperse the iron ion-doped titanium dioxide nanomaterials well, causing the nanomaterials to agglomerate.
[0109] Comparative Example 3
[0110] This comparative example provides a method for preparing a spectacle lens, which differs from Example 4 in that if step (3) is omitted, the lens cannot be formed.
[0111] The finished spectacle lenses were tested for surface mechanical properties. The test results are shown in Table 1.
[0112] Table 1 Lens surface mechanical properties test results
[0113]
[0114] Note: In Table 1, the technical requirements for compressive strength are: after testing according to the method specified in ISO12312-1, the lens should not break or deform; the impact resistance is tested according to the method specified in QB / T2506-2017, and the lens meets the requirements if any of the following conditions do not occur: 1. The lens is cracked into two or more pieces; 2. Fragments fall off the near-eye surface of the lens; 3. The lens is penetrated; the technical requirement for surface hardness is 30±2.
[0115] According to the above examples and comparative examples, it is known that:
[0116] Example 4 is the best example. Referring to Table 1, when the doping ratio of iron atoms is 3.43%, the iron-titanium bimetallic oxide nanomaterial with this ratio is used to prepare eyeglass lenses. The absorption rate of ultraviolet light is 100%, and the absorption rate of high-frequency blue light (400nm to 430nm) is as high as more than 99%. It can effectively filter out the damage to the eyes caused by the blue light of electronic products and prevent the occurrence of a series of eye diseases such as dry eyes.
[0117] Comparison of Example 4, Example 5 and Example 6 shows that increasing the amount of the iron-titanium bimetallic oxide nanomaterial, that is, the mass ratio of the iron-titanium bimetallic oxide nanomaterial to the monomer increases, Figure 4 , Figure 5 and Figure 6 The increase in the amount of nanomaterial added will affect the transmittance of the final prepared eyeglasses to visible light with a wavelength of 500nm to 700nm. Therefore, the amount of iron-titanium bimetallic oxide nanomaterial added should be controlled. The mass ratio of iron-titanium bimetallic oxide nanomaterial to monomer is 1:1000, which has the best effect.
[0118] Comparison of Examples 4 to 6 with Examples 7 to 9 shows that Figures 4 to 9 Compared with the lenses made from acrylate monomers, the lenses made from epoxy acrylate monomers have a slightly lower transmittance to visible light of 450-550nm and a slightly lower surface hardness. Therefore, the transmittance and mechanical properties of the lenses made from epoxy acrylate monomers are not as good as those of the lenses made from acrylate monomers.
[0119] Comparison of Comparative Example 1 with Example 4 shows that the spectacle lenses are prepared by directly mixing the iron oxide nanopowder and the titanium dioxide nanopowder in an equal amount as the titanium dioxide nanomaterial doped with iron ions in Example 4. Fig.10 , its visible light transmittance of 450-650nm is significantly reduced, which will affect the normal use of the eyeglasses. That is, the titanium dioxide nanomaterial doped with iron ions in Example 4 can effectively avoid the influence of direct use of iron oxide nanopowder on the color of the eyeglasses.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A blue light protection nanomaterial, characterized in that: Titanium dioxide doped with iron ions, wherein the total content of iron atoms is 1%-4%; The particle size of the nano material is 20-50 nm.
2. A spectacle lens, characterized in that: It comprises the blue light protection nano material and polymer optical substrate as claimed in claim 1; The anti-blue light nanomaterial is uniformly dispersed in the polymer optical substrate, wherein the mass ratio of the anti-blue light nanomaterial to the polymer optical substrate is 1-3‰.
3. The spectacle lens according to claim 2, characterized in that: The polymer optical substrate is one or more of methacrylate resin, polyurethane resin, allyl diglycol dicarbonate resin, acrylate resin and epoxy acrylate resin.
4. The spectacle lens according to claim 2, characterized in that: It also includes an ultraviolet absorber in an amount of 1-4‰ of the mass ratio of the polymer optical substrate.
5. The spectacle lens according to claim 4, characterized in that: The ultraviolet absorber is a fat-soluble ultraviolet absorber, selected from one or more of UV-326, UV-327, UV-329, UV-360, and UV-531.
6. The spectacle lens according to claim 2, wherein: It also includes an initiator whose mass ratio to the polymer optical substrate is 1-3‰; The initiator is selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, diisopropyl peroxydicarbonate, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, methyl benzoylformate, benzoin dimethyl ether, diphenylacetone, α-aminoalkylphenone, dibenzoylphenylphosphine oxide, benzophenone and isopropylthioxanthone; and a dispersion medium accounting for 10-15‰ of the mass ratio of the polymer optical substrate; The dispersion medium is styrene.
7. A method for preparing a spectacle lens as claimed in claim 2, characterized in that: The following steps are involved: S1. Dispersion of anti-blue light nanomaterials: mixing the anti-blue light nanomaterials with a liquid dispersion medium to obtain an anti-blue light nanomaterial dispersion liquid; S2, the first curing reaction: the dispersion liquid is stirred and mixed with the polymer optical monomer and the initiator, and then vacuum degassing is performed, the lens is put into a mold, and the lens is cured according to the first temperature rising program, and the lens is demolded to obtain a primary lens; S3, second curing reaction: the primary lens is put into the mold again, and cured according to the second temperature rising program to obtain a spectacle lens containing blue light blocking nanomaterials.
8. The method for preparing a spectacle lens according to claim 7, characterized in that: In S1, the mass ratio of the blue light blocking nanomaterial to the dispersion medium is 1-3:10; The process of mixing the blue light protection nanomaterial with the dispersion medium is: heating to 70-90° C. while stirring, and then ultrasonically dispersing for 40-50 minutes.
9. The method for preparing a spectacle lens according to claim 7, characterized in that: In S2, the polymer optical monomer is selected from one or more of methacrylate monomers, polyurethane monomers, allyl diglycol dicarbonate monomers, acrylate monomers, and epoxy acrylate monomers.
10. The method for preparing a spectacle lens according to claim 7, characterized in that: In S2, the first temperature program is the gelation stage; In S3, the second temperature rising program is the post-curing stage.
Citation Information
Patent Citations
Method for preparing nanometer particle with iron-doped nanometer titanium dioxide / silicon dioxide nuclear shell structure
CN102205418A
Blue light cut nano compound resin material, lens and preparation method thereof
CN103980643A
Anti-blue light nanometer composite monomer material and anti-blue light optical resin prepared from same
CN103992422A
Method for preparing iron-doped rutile titanium dioxide
CN104248955A
Anti-blue-ray nano composite microsphere, anti-blue-ray optical resin material and preparation method thereof
CN109331754A